THE IMPLEMENTATION OF QUANTUM THINKER MODEL IN TEACHING READING - Ansas, Vegayanto Abdurrakhman Alfikri (2015)
Knowing a beneficial reading model for teachers is essential due to the unvaried and passive reading teaching. It is also important since it deals with students' inability to comprehend an English text sufficiently. Therefore, this study was aimed to investigate how Quantum Thinker model by DePorter as a reading model was implemented in teaching reading to eleventh-grade of senior high school students. Nine eleventh-grade students of senior high school in Bandung were involved in this study. This study employed case study as the methodology. The data were gained from classroom observation, teacher's field notes, and interview. The findings revealed that the implementation of Quantum Thinker model was considered as an appropriate and effective model in teaching reading. Quantum Thinker model began with the opening of the class conducted by the teacher, then reading the title of the text, making questions, finding ideas, relating the title of the text to the students' experiences, and reading and discussing the text. It helped the teacher to teach in ease situation, particularly in engaging the students engagement and participation, managing class, and creating a great atmosphere. Moreover, the findings indicated that Quantum Thinker model also developed the students' enthusiasm and creativity in the learning process, and encouraged them to improve their reading ability. In other words, the implementation of Quantum Thinker model had significant influence toward the students' reading ability. However, facilitating students' characteristics and providing supporting media and guidance are also essential in implementing Quantum Thinker model in teaching reading. Keywords: Quantum Thinker, Teaching Reading. Mengetahui sebuah model membaca yang bermanfaat merupakan hal yang penting bagi guru dikarenakan oleh ketidakvariatifan dan kepasifan pengajaran membaca. Hal ini menjadi penting karena berkaitan dengan ketidakmampuan siswa untuk memahami dengan cukup sebuah teks berbahasa Inggris. Maka dari itu, penelitian ini ditujukkan untuk menginvestigasi bagaimana model Quantum Thinker sebagai model membaca diimplementasikan dalam pengajaran membaca ke siswa Sekolah Menengah Atas (SMA) kelas 11. 9 siswa SMA kelas 11 di Bandung dilibatkan dalam penelitian ini. Penelitian ini menggunakan metodologi Studi Kasus. Data diambil dari observasi kelas, catatan guru, dan wawancara. Hasil penelitian menunjukkan bahwa pengimplementasian model Quantum Thinker dipertimbangkan menjadi sebuah model yang sesuai dan efektif dalam pengajaran membaca. Model Quantum Thinker dimulai dari pembukaan kelas yang dipimpin oleh guru, kemudian pembacaan judul teks, pembuatan pertanyaan, penemuan ide, perhubungan antara judul teks dengan pengalaman siswa, dan pembacaan dan diskusi teks. Pengimplementasian model Quantum Thinker ini membantu guru untuk mengajar di dalam situasi yang mudah, khususnya dalam keikutsertaan dan partisipasi siswa, manajemen kelas, dan pembuatan atmosfir yang bagus. Selain itu, hasil temuan menunjukkan bahwa model Quantum Thinker mengembangkan antusiasme dan kreatifitas siswa di dalam proses belajar, dan mendorong siswa untuk meningkatkan kemampuan membaca. Dengan kata lain, pengimplementasian model Quantum Thinker memiliki pengaruh yang signifikan terhadap kemampuan membaca siswa. Akan tetapi, memfasilitasi karakteristik siswa dan menyediakan media dan bimbingan yang mendukung merupakan hal yang penting dalam mengimplementasikan model Quantum Thinker di pengajaran membaca. Kata kunci: Quantum Thinker, Teaching Reading.